PERLINDUNGAN HUKUM TERHADAP PEMBELI BERITIKAD BAIK DARI JERAT PIDANA PENADAHAN DALAM TRANSAKSI MEDIA SOSIAL - Adi Wijaya; Eli Tri Kursiswanti; Muhammad Arganata Thamrin (Collegium Studiosum Journal, 2026)
The rise of second hand goods transactions through social media has created a fast, inexpensive, and accessible economic space. Nevertheless, it also produces a risk of criminalisation against buyers who temporarily possess goods later alleged to originate from a crime. This article examines legal protection for good faith purchasers in second-hand mobile phone transactions conducted through social media, particularly when the transaction occurs through cash on delivery, the device is locked, the seller applies pressure, and the buyer pays a down payment merely to avoid further conflict. This research applies a normative juridical method using statutory, conceptual, and normative case-study approaches. The article argues that receiving stolen goods under Article 591 of Law Number 1 of 2023 on the National Criminal Code cannot be established solely by physical possession. Investigators must prove the subjective element that the buyer knew or should reasonably have suspected that the goods originated from a crime. Defects of consent caused by intimidation, pressure, and deception may undermine the mens rea element. Investigators must also verify the predicate crime, lawful owner, IMEI or item identity, and electronic transaction records before directing a buyer as a suspect. This article proposes a due-diligence-based evidentiary model and stronger procedural safeguards to prevent the criminalisation of good faith purchasers.